Kiprah Nabi Muhammad Memberantas Perdagangan Manusia - Nurhamid Nurhamid (PSGA LP2M IAIN Pontianak, 2017)
Human Trafficking, in fact, has been occured before Islamic era, such as slavery that has been practiced for years. It is not a surprise that human trafficking in 20th century is not a new thing. There are so many factors triggered this slavery happened; genetics’ factor, war’s prisoner, poverty, working in others’ land, abduction, vengeance, and so on. Furthermore, slavery itself is not a willingnes, yet a life necessity and compulsion. Moreover, Islam as a universal religion is against the human trafficking badly. In Islam, all of human have similar position in front of Allah SWT, what makes it difference is the beliefs level. Therefore, one of the story in Islamic hostory is to eradicate the slavery on fathwatul makkah.